Тетрадки под дождем: рассказы и повести / В. В. Голявкин - Голявкин В. В. (Школьная библиотека, 2005)
Экземпляры: (20190704) / Инвентарный номер: 31867 / Цена: 85.50 / Сис.шифр: Р2 / Авт.знак: Г63 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6